2022
DOI: 10.3390/healthcare10030488
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Depression in Medical Students in a Northern Thailand University: A Cross-Sectional Study

Abstract: This study was conducted to investigate the prevalence and associated factors of depression in medical students. This cross-sectional study investigated the prevalence and associated factors of depression in medical students from May 2018 to April 2019. Depression was diagnosed using the nine-item Patient Health Questionnaire. We evaluated the following potential predictors: demographic data, stressors, psychiatric comorbidities, emotional intelligence (EI), and perceived social support. The association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
(54 reference statements)
2
11
0
Order By: Relevance
“…The prevalence of depression in the present study was higher than in prior studies [ Akhtar et al, 2020;Pacheco et al, 2017;Rotenstein et al, 2016], likely because the participants were recruited from the mental health service. However, the anxiety rate was similar to earlier studies [Phomprasith et al, 2022]. Additionally, the three most common mental health problems presented in the service are similar to those in the community-based study of Thai university students [Chiddaycha and Wainipitapong, 2021].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The prevalence of depression in the present study was higher than in prior studies [ Akhtar et al, 2020;Pacheco et al, 2017;Rotenstein et al, 2016], likely because the participants were recruited from the mental health service. However, the anxiety rate was similar to earlier studies [Phomprasith et al, 2022]. Additionally, the three most common mental health problems presented in the service are similar to those in the community-based study of Thai university students [Chiddaycha and Wainipitapong, 2021].…”
Section: Discussionsupporting
confidence: 85%
“…In addition, examples of common mental health problems in university students are stress [Pacheco et al, 2017], burnout [Pacheco et al, 2008], sleep problems [Azad et al, 2015;Chinvararak et al, 2021], depression [Tung et al, 2018, Pacheco et al, 2017, anxiety [MacLean et al, 2016;Pacheco et al, 2017], and suicidal ideation [Pacheco et al, 2008]. Prior studies showed that the prevalence of depression in medical students globally and in Thailand ranged between 2-30% [Rotenstein et al, 2016;Phomprasith et al, 2022], while the anxiety rate was approximately 6-78% [Puthran et al, 2016]. Other psychiatric disorders, such as obsessive-compulsive disorder (OCD) and substance use disorder, were also found [Pacheco et al, 2017].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of suicide and suicidal thoughts is an old issue in the medical world, and this issue is still one of the things that are highlighted and hidden because of the bad stigma attached to doctors or medical students with mental emotional problems. Research on this subject has always consistently shown that medical students have a high prevalence of depression, burnout, and emotional disorders, as well as a higher risk of having suicidal thoughts [9][10][11]. The risk of suicidal thoughts is associated with several factors, including individual factors, family and academic situations.…”
Section: Suicide and Risk Factors In Medical Studentsmentioning
confidence: 99%
“…Depression is a serious medical illness that can decrease a person’s ability to function [ 2 , 3 ]. Depressed medical students may present with a decrease in educational performance, hopelessness and excessive sadness [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depression is a serious medical illness that can decrease a person’s ability to function [ 2 , 3 ]. Depressed medical students may present with a decrease in educational performance, hopelessness and excessive sadness [ 3 , 4 ]. The prevalence of depression among medical students worldwide was estimated at 27.2% [ 3 , 5 ], with even higher rates found among Lebanese students (34.4%) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%